2002
DOI: 10.1002/j.2158-1592.2002.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Logistics Strategy — Revisited

Abstract: This research addresses the roles of three logistics strategies in achieving logistics effectiveness, explores the interaction among these three strategies, and discusses the role of logistics strategy in managing conflicting challenges inherent in logistics. This article is organized into five sections. The following section reviews the literature and develops hypotheses. Next, the methodology section describes the data collection process. Third, the data analysis and results are described. The fourth section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 2 publications
0
47
0
4
Order By: Relevance
“…Let us start with the globalisation of supply chains, which has prompted many firms to develop logistics as part of their corporate strategy (McGinnis and Kohn, 2002). One effect of this is the fact that logistics has been given a more prominent and strategic role within many companies (Zacharia and Mentzer, 2007).…”
Section: List Ofmentioning
confidence: 99%
“…Let us start with the globalisation of supply chains, which has prompted many firms to develop logistics as part of their corporate strategy (McGinnis and Kohn, 2002). One effect of this is the fact that logistics has been given a more prominent and strategic role within many companies (Zacharia and Mentzer, 2007).…”
Section: List Ofmentioning
confidence: 99%
“…During the literature search a number of articles were found that elaborated on logistics strategies without discussing business strategy, and these were consequently kept outside the scope of the search. For instance, McGinnis and Kohn (2002) with the title "Logistics strategy -Revisited", discusses logistics strategy in terms of process, market and information, was rejected because it was not based on general business strategy.…”
Section: The Theoretical Framework On Strategymentioning
confidence: 99%
“…Market dynamics has significant contingent effects on the formation and execution of business strategy, and on the design and implementation of operations processes/systems (Venkatraman and Prescott 1990;Leong et al 1990;McGinnis and Kohn 2002). Market dynamics can be operationalized as the dynamics of source and demand, the environment stability, the level of industrial competition, or the life-cycle of technology.…”
Section: Contextual Variablementioning
confidence: 99%